Educating young people to mobilize agriculture - Egbenayabuma, Friday (Technical Centre for Agricultural and Rural Cooperation, 1995)
In the so-called developed countries, where agriculture and industrial revolutions occurred up to two or more centuries ago, there was an early awareness that education should be related to the needs of the population, including farmers. This...